The Weimar Republic Sourcebook - Dimendberg, Edward; Jay, Martin; Kaes, Anton (Berkeley, CA : University of California Press, 2020)
Reproduces (translated into English) contemporary documents or writings with an introduction to each section.
Frontmatter -- Contents -- Preface -- 1. The Legacy of the War -- 2. Revolution and the Birth of the Republic -- 3. Economic Upheaval: Rationalization, Inflation, and Depression -- 4. Coming to Terms with Democracy -- 5. The Rise of Nazism -- 6. The Struggle against Fascism -- Pictures -- 7. White-Collar Workers: Mitlelsland or Middle Class? -- 8. The Rise of the New Woman -- 9. Forging a Proletarian Culture -- 10. The Jewish Community: Renewal, Redefinition, Resistance -- Pictures -- 11. Redefining the Role of the Intellectuals -- 12. Critical Theory and the Search for a New Left -- 13. Revolution from the Right -- 14. Cultural Pessimism: Diagnoses of Decline -- Pictures -- 15. Imagining America: Fordism and Technology -- 16. Berlin and the Countryside -- 17. Designing the New World: Modern Architecture and the Bauhaus -- 18. Housing for the Masses -- 19. From Dada to the New Objectivity: Art and Politics -- Pictures -- 20. Literature: High and Low -- 21. Theater, Politics, and the Public Sphere -- 22. The Roaring Twenties: Cabaret and Urban Entertainment -- 23. Music for Use: Gebrauchsmusik and Opera -- 24. New Mass Media: Radio and Gramophone -- 25. Cinema from Expressionism to Social Realism -- Pictures -- 26. Visual Culture: Illustrated Press and Photography -- 27. Visions of Plenty: Mass Consumption, Fashion, and Advertising -- 28. The Cult of the Body: Lebensreform, Sports, and Dance -- 29. Sexuality: Private Rights versus Social Norms -- 30. On the Margins of the Law: Vice, Crime, and the Social Order -- Biographies -- Political Chronology -- Selected Bibliography -- Acknowledgments -- Index
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 01. Okt 2020).
JSTOR
Keywords: Germany -- Politics and government -- 1918-1933 -- Sources; Germany -- Social conditions -- 1918-1933 -- Sources; Germany -- Social life and customs -- 20th century -- Sources; National socialism -- Sources; Government, Resistance to -- Germany -- History -- 20th century -- Sources; National socialism -- Sources; Government, Resistance to -- Germany -- History -- 20th century -- Sources; Germany -- Social conditions -- 1918-1933 -- Sources; Germany -- Social life and customs -- 20th century -- Sources; Nazisme -- Sources; Résistance au gouvernement -- Allemagne -- Histoire -- 20e siècle -- Sources; Allemagne -- Politique et gouvernement -- 1918-1933 -- Sources; Allemagne -- Conditions sociales -- 1918-1933 -- Sources; Allemagne -- Mœurs et coutumes -- 20e siècle -- Sources; Allemagne -- Conditions sociales -- 1918-1933 -- Sources; Allemagne -- Mœurs et coutumes -- 20e siècle -- Sources; Nazisme -- Sources; Résistance au gouvernement -- Allemagne -- Histoire -- 20e siècle -- Sources; HISTORY / Europe / General; Social conditions; Politics and government; National socialism; Manners and customs; Government, Resistance to; Germany; Deutschland; Weimar-republiek.; Allemagne -- Vie intellectuelle -- 1918-1945 -- Sources; Allemagne -- 1918-1933 (République de Weimar) -- Sources; Allemagne -- Conditions sociales -- 1918-1933 -- Sources; Allemagne -- Politique et gouvernement -- 1918-1933 -- Sources; 1900-1999; History; Sources